Regional and international integration and modes of governance : the Caribbean case - Lewis, Vaughn (2001)
Examines the functioning of the regional integration structures of the Caribbean Community and the Common Market as they have evolved from their establishment to the present time. Seeks to demonstrate how governments involved in the integration exercise tried to adapt to changing domestic and external circumstances. Indicates that in some measure, the process of the deepening of the integration system has been a halting one. Examines the options placed before governments in the widening of the boundaries of the system, in the recent past. Looks at possible options for consideration in the present as they respond dynamically to changing regional and international environments.